Normal Adrenal Gland Thickness on Computed Tomography in Nepalese Adults Presenting to Tertiary Referral Hospital - Devkota, Karun; Adhikari, Kapil; Koirala, Sapana; Chapagain, Ashok; Bhandari, Sandeep; Rauniyar, Ramhari (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Various benign and malignant conditions may alter the morphology and dimensions of adrenal gland. There is limited data on normal dimensions of adrenal gland in Nepalese population. Our study aimed to find out the normal adrenal gland thickness measurement. Methods: It is a descriptive cross-sectional study conducted in a tertiary referral hospital over a period of one year. Ethical approval was taken from the institutional review committee. All the patients referred to Radiology Department for abdominal Computed Tomography evaluation unrelated to adrenal pathology were included. We measured maximum thickness of adrenal limb and body along with diaphragmatic crus on either side. Results: Mean adrenal gland thickness of right medial limb, right lateral limb and body was 3.57 ± 0.87 mm, 3.33 ± 0.79 mm, 5.69 ± 1.19 mm respectively. Similarly, mean adrenal gland thickness of left medial limb, left lateral limb and body was 4.16 ± 0.9 mm, 3.84 ± 0.85 mm, 6.07 ± 1.35 mm respectively. On comparison of medial and lateral limbs to ipsilateral diaphragmatic crus thickness, 298 (99.3%) and 296 (98.6 %) cases had ratio less than one on right side and 280 (93.3%) and 268 (89.3 %) cases had ratio less than one on left side. Conclusions: Our study has established the reference measurement of normal adrenal gland thickness in Nepalese adult population. Similarly, the ratio of adrenal limb thickness to ipsilateral diaphragmatic crus thickness can also be a helpful parameter for predicting the normality.